Eating clean for dummies - Wright, Jonathan V.; Larsen, Linda Johnson (Hoboken, New Jersey John Wiley & Sons, Inc., 2016)
Used as a way of life, clean eating can improve overall health, prevent disease, increase energy and stabilize moods. Provides the reader with an-easy-to-follow guide to eliminate processed foods from one's diet and improve one's health and budget by eating clean--Source other than Library of Congress.
Eating clean: it does a body good -- Meeting your eating clean goals -- Planning and preparing your eating clean adventure -- Adapting the eating clean plan to fit your life -- Morning to evening recipes -- The part of tens.
"Learning made easy"--Cover.
Keywords: Nutrition; Food habits